On Ocean Boulevard [large type] - Monroe, Mary Alice (Monroe, Mary Alice. Beach house series, 2020)
It's been sixteen years since Caretta "Cara" Rutledge has returned home to the beautiful shores of Charleston, South Carolina. Over those years, she has weathered the tides of deaths and births, struggles and joys. And now, as Cara prepares for her second wedding, her life is about to change yet again. Meanwhile, the rest of the storied Rutledge family is also in flux. But as excitement over the house and wedding builds, a devastating illness strikes the family and brings plans to a screeching halt. It is under these trying circumstances that the Rutledge family must come together yet again to discover the enduring strength in love, tradition, and legacy from mother to daughter to granddaughter..